Chemoprevention assessment, genotoxicity and cytotoxicity of flavonoids from Inga laurina leaves (FABACEAE) - Sanzovo, T. O.R. [UNESP]; Lima, N. M. [UNESP]; Marqui, S. R. [UNESP]; Andrade, T. J.A.S.; Navegante, G. [UNESP]; Serafim, R. B. [UNESP]; Sorbo, J. M. [UNESP]; Valente, V. [UNESP]; Silva, D. H.S. [UNESP]; Soares, C. P. [UNESP] (Taylor & Francis, 2019)
This study aimed to identify and evaluate the cytotoxicity, genotoxicity, antigenotoxicity and chemoprevention assessment of flavonoids myricetin-3-O-(2″-O-galloyl)-α-rhamnopyranoside and myricetin-3-rhamnoside from Inga laurina leaves extract. The Quinone reductase induction as a biomarker for cancer chemoprevention was evaluated in murine hepatocellular carcinoma, the cytotoxicity was evaluated by sulforhonamide B assay and genotoxicity was evaluated by comet assay using HepG2 cell line. The results demonstrated that the flavonoids didn´t show cytotoxicity in HepG2 cells. In the chemoprevention evaluations were not able to promote the induction of Quinone Reductase and also no genotoxic effect was observed by evaluation of the comet assay in none of the concentrations tested. In the antigenotoxicity test, all compounds had a protective effect against damage induced by hydrogen peroxide and were repaired against damage. Although none of the flavonoids were capable of inducing the enzyme Quinone Reductase at the concentrations tested, the antigenotoxicity results showed a powerful chemoprotective action.
Keywords: chemoprevention; cytotoxicity; Flavonoids; genotoxicity; Inga laurina